Study of behavior nanoclusters of ethanol in cryomatrix nitrogen depending on the temperature and concentration - Kurnosov, V.; Katpaeva, K.; Sokolov, D.; Kubetaeva, A. (Recent Contributions to Physics, 2014)
Earlier research molecular processes recondensation ethanol cryomatrix nitrogen on to the substrate found that the state of the molecules of ethanol in the matrix is not stable. A slight increase of temperature of the solid nitrogen long before its sublimation changes the vibrational spectrum of the bicomponent film ethanolnitrogen. The results of study of this phenomenon are presented here. The measurements were carried out in the temperature range 12-40K at the initial vacuum in the chamber of at least 10-8 Torr. The concentration of ethanol in nitrogen was from0.5% to 3%.